Transcranial magnetic stimulation in mild to severe hemiparesis early after stroke: a proof of principle and novel approach to improve motor function - Conforto, Adriana B. (J Neurol, 2011)
Low-frequency repetitive transcranial magnetic stimulation (rTMS) of the unaffected hemisphere can enhance function of the paretic hand in patients with mild motor impairment. Effects of low-frequency rTMS to the contralesional motor cortex at an early stage of mild to severe hemiparesis after stroke are unknown. In this pilot, randomized, double-blind clinical trial we compared the effects of low-frequency rTMS or sham rTMS as add-on therapies to outpatient customary rehabilitation, in 30 patients within 5–45 days after ischemic stroke, and mild to severe hand paresis. The primary feasibility outcome was compliance with the interventions. The primary safety outcome was the proportion of intervention-related adverse events. Performance of the paretic hand in the Jebsen–Taylor test and pinch strength were secondary outcomes. Outcomes were assessed at baseline, after ten sessions of treatment administered over 2 weeks and at 1 month after end of treatment. Baseline clinical features were comparable across groups. For the primary feasibility outcome, compliance with treatment was 100% in the active group and 94% in the sham group. There were no serious intervention-related adverse events. There were significant improvements in performance in the Jebsen–Taylor test (mean, 12.3% 1 month after treatment) and pinch force (mean, 0.5 Newtons) in the active group, but not in the sham group. Low-frequency rTMS to the contralesional motor cortex early after stroke is feasible, safe and potentially effective to improve function of the paretic hand, in patients with mild to severe hemiparesis. These promising results will be valuable to design larger randomized clinical trials.